SIgA and Upper Respiratory Syndrome During a College Cross Country Season - Fahlman, Mariane M.; Engels, Hermann J.; Hall, Heather (Sports Medicine International Open, 2017)
We examined the changes in salivary immunoglobulin A (SIgA) and the incidence of upper respiratory syndrome (URS) throughout a college cross-country season as well as the acute effect of a VO2max test on SIgA. Subjects were 22 cross country athletes (XC) (20.7±0.3 years) and 23 matched controls (C) (20.4±0.2 years). Saliva samples were collected pre and post VO2max and at four training time points (August – November). Weekly logs indicating S&S of URS from which a total symptom score (TSS) was calculated were collected. There was a significant decrease in SIgA F(1,43)=10.742, p<0.001 and the secretion rate of SIgA F(1,43)=15.617, p<0.001 for XC at time points two through four. XC was also significantly lower than controls in those two variables across those time points. The secretion rate of SIgA and URS were negatively correlated at time point four R2=0.443, F(4,22)=26.9, p=0.001. There was a significant acute post exercise decrease in the secretion rate of SIgA, pre (M=21.44, SEM=3.95) and post (M=14.5, SEM=3.0), t(1,21)=2.185, p=0.039. Prolonged training resulted in decreased mucosal SIgA.
Keywords: mucosal Immunity; excessive training; illness; immunoglobulins